Dental bulk block and manufacturing method thereof
A dental bulk block with a gradient of lithium disilicate and eucryptite crystal phases addresses the challenges of machining and color replication in artificial teeth, enhancing machinability and structural stability for efficient production of aesthetically pleasing prosthetics.
Patent Information
- Application Number
- JP2022549869
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-15
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-06-15
AI Technical Summary
Existing dental materials, such as lithium disilicate crystallized glass, have coarse crystalline phases that are difficult to machine, leading to poor dimensional accuracy and limited ability to achieve high light transmittance and opalescence similar to natural teeth, while conventional CAD/CAM methods struggle to replicate the multi-gradation color of natural teeth.
A dental bulk block composed of a glass-ceramic material with a gradient of lithium disilicate and eucryptite crystal phases, allowing for adjustable transparency and mechanical properties through controlled heat treatment, enabling precise machining and replication of natural tooth characteristics.
The dental bulk block achieves multi-gradation transparency and mechanical properties similar to natural teeth, facilitating efficient manufacturing of artificial teeth with improved machinability and structural stability, reducing processing time and complexity.
Smart Images

Figure 0007605506000004 
Figure 0007605506000005 
Figure 0007605506000006
Abstract
Description
[Technical Field]
[0001] The present invention relates to a dental bulk block useful for producing artificial teeth that resemble the structural characteristics of natural teeth, and in particular to a dental bulk block with improved machinability, and a method for producing the same. [Background technology]
[0002] Crown materials are prosthetic materials used to restore damaged dentin and enamel. They are classified as inlays, onlays, veneers, crowns, and other types depending on the application site. Because crown materials are used to restore the outer surface of a tooth, they require high aesthetic properties and high strength to prevent breakage due to wear from opposing teeth or chipping. Conventional crown materials include leucite glass-ceramics, reinforced porcelain, and fluorapatite (Ca5(PO4)3F) glass-ceramics. While these materials offer excellent aesthetic properties, they have the disadvantage of being prone to fracture due to their low strength (80-120 MPa). For this reason, research is currently underway to develop high-strength crown materials made from a variety of materials.
[0003] Lithium silicate glass-ceramics were introduced in 1973 by Marcus P. Borom and Anna M. Turkalo at the Pacific Coast Regional Meeting, The American Ceramic Society, San Francisco, CA, October 31, 1973 (Glass division, No. 3-G-73P).
[0004] The crystalline phase and strength of Li2O-Al2O3-SiO2-Li2O-K2O-B2O3-P2O5 glasses were investigated under various crystal nucleation and growth heat treatment conditions. The strength of glasses exhibited 30-35 kPS when they exhibited low-temperature lithium metasilicate or high-temperature lithium disilicate crystalline phases. This was due to residual stress resulting from the difference in thermal expansion coefficients between the base glass, mother glass, Li2SiO5, and Li2SiO3 phases.
[0005] Numerous patents have already disclosed materials and methods for fabricating artificial teeth (monolithic dental crowns) using glass containing lithium disilicate crystals. However, these technologies are difficult to machine due to the large size of the crystalline phase. Therefore, machining requires a primary process of forming a machinable crystalline lithium metasilicate, followed by a secondary heat treatment to form a high-strength lithium disilicate crystalline phase. This process results in poor dimensional accuracy due to shrinkage during the post-heat treatment process, and the additional heat treatment step is inconvenient. Generally, CAD / CAM-based prosthetic fabrication requires direct machining of a bulk prosthesis in the hospital, which must then be tried on the patient as quickly as possible (one-day appointment). The time delays associated with the heat treatment process create financial hardships for patients and users.
[0006] Furthermore, conventional lithium disilicate glass-ceramic materials have limitations in achieving high light transmittance and opalescence similar to that of natural teeth due to the coarse crystalline phase.
[0007] In particular, conventional lithium disilicate glass-ceramics materials are primarily made into easily processable lithium metasilicate glass-ceramics for processing, and then after processing, lithium disilicate is formed through a secondary crystallization heat treatment to increase strength. At this time, the size of the crystalline phase is approximately 3 μm or more, and in this state, processability is significantly reduced, and only strength is achieved.
[0008] To solve this problem, the applicant proposed a method for manufacturing crystallized glass containing lithium disilicate crystal phase and silicate crystal phase, which has excellent processability by adjusting the crystal size through the change of the primary heat treatment temperature, and has already received a patent (Korean Patent No. 10-1975548). Specifically, the present invention discloses a method for producing dental glass-ceramics containing a silica crystalline phase, which comprises the steps of: subjecting a glass composition containing 60-83 wt% SiO2, 10-15 wt% Li2O, 2-6 wt% P2O5 acting as a nucleating agent, 1-5 wt% Al2O3 which increases the glass transition temperature and softening point and enhances the chemical durability of the glass, 0.1-3 wt% SrO which increases the softening point of the glass, 0.1-2 wt% ZnO, 1-5 wt% colorant, and 2.5-6 wt% Na2O+K2O, which are alkali metal oxides which increase the thermal expansion coefficient of the glass, to a first heat treatment at 400°C to 850°C; and subjecting the glass composition to a second heat treatment at 780°C to 880°C after the first heat treatment; wherein the first heat treatment produces a lithium disilicate crystalline phase and a silica crystalline phase with nano-sized particles of 5 nm to 2000 nm, and the translucency is controlled by the temperature of the second heat treatment.
[0009] On the other hand, as human living standards improve, the demand for aesthetics is also increasing in the field of dentistry, and as patients' aesthetic desires gradually increase, much research is being conducted on aesthetic prosthetic restorations using various materials.
[0010] The factors that affect the aesthetics of porcelain restorations, which are currently the most widely used aesthetic restorative materials, include the tooth's outer shape, surface condition, transparency, and color, with transparency being particularly important for successful restorations. Although much research and development has been done on the mechanical and physical properties of porcelain for aesthetic prostheses, there are still many issues with color matching, and clinical and technical difficulties exist in selecting the color of restorations, especially transparency.
[0011] In aesthetic prosthetics, factors that affect the aesthetics of dental restorations include color, tooth shape and size, tooth alignment and proportions, light, transparency, and restoration design. In fact, the factors that the human eye is most sensitive to are color and shape.
[0012] No part of a natural tooth has the same color from the neck to the incisal edge of the tooth.
[0013] Reflecting this, in recent years, a method for manufacturing artificial teeth that can imitate the deep color of natural teeth using a so-called build-up method has become known.
[0014] The build-up method involves layering powders such as porcelain or zirconia to form artificial teeth that are given a color tone, and then heat-treating the resulting artificial teeth to achieve a layered color similar to that of natural teeth.Although this method can closely mimic the color of natural teeth, the aesthetic appeal of the artificial teeth is determined entirely by the skill of the dental technician, which means that it is not very reproducible, cannot be manufactured in an instantaneous manner, is not beneficial to patients, and is difficult to achieve with machining methods such as CAD / CAM.
[0015] On the other hand, when artificial teeth are made using conventional bulk blocks through cutting processes such as CAD / CAM, the bulk blocks themselves are made of materials with uniform physical properties, so the resulting artificial teeth have no choice but to be obtained in a single color tone, unlike natural teeth. In particular, artificial teeth made using this method have the problem of appearing aesthetically strange and unnatural when applied to front teeth, etc.
[0016] Even with the method for manufacturing crystallized glass disclosed in Korean Patent No. 10-1975548 by the applicant, it is possible to adjust transparency and workability through a secondary heat treatment process, but the resulting crystallized glass is a single block with the same physical properties, and in order to achieve a deep color similar to that of natural teeth using it, it is necessary to apply a method of combining multiple results. In other words, it is not easy to instantly achieve natural-colored teeth by directly applying cutting processes such as CAD / CAM using the bulk block itself.
[0017] To improve on this issue, the applicant has filed and already received a patent for a bulk block (Korean Patent No. 10-2246195) that is useful for manufacturing artificial tooth prostheses that resemble natural teeth, thereby shortening the time and process for manufacturing the artificial tooth prostheses, and that can bring about the effect of increased structural stability in terms of force distribution due to the gradient function of mechanical properties.
[0018] The present invention has been devised to provide a gradation bulk block that has improved aesthetics and, in particular, improved machinability compared to such bulk blocks. Summary of the Invention [Problem to be solved by the invention]
[0019] The present invention aims to provide a dental bulk block that can be used to manufacture artificial tooth restorative materials that exhibit multi-gradation transparency or physical properties similar to those of natural teeth, so that they can be repeatedly reproduced through cutting processes such as CAD / CAM without the need for additional processes.
[0020] In addition, the present invention aims to provide a dental bulk block that not only has improved machinability, thereby shortening the time and process required to manufacture artificial tooth prostheses, but also has the effect of increasing structural stability in terms of force distribution due to the functional gradient of mechanical properties.
[0021] The present invention also provides a method for easily producing a dental bulk block that can be used to produce an artificial tooth restorative material that exhibits multi-gradation transparency or physical properties similar to those of natural teeth.
[0022] The present invention also aims to provide a method for easily manufacturing such a dental bulk block into a dental restoration using a processing machine. [Means for solving the problem]
[0023] One embodiment of the present invention provides a dental bulk block, which is a glass-ceramic block comprising a crystalline phase within an amorphous glass matrix, the crystalline phase being a functionally graded material having a gradient in the size of the primary crystal phase with respect to depth, with no interfaces present at the locations where the gradient value of the primary crystal phase size changes, the crystalline phase being a predominantly lithium disilicate and an additional crystalline phase comprising eucryptite.
[0024] In a preferred embodiment of the present invention, the gradient in the size of the main crystal phase can be realized within the range of an average grain size of 0.02 μm to 1.5 μm.
[0025] A dental bulk block according to an embodiment of the present invention may have a gradient of light transmittance with respect to depth.
[0026] In a preferred embodiment, the gradient of the light transmittance may be in the range of 22 to 35% based on a wavelength of 550 nm.
[0027] In a preferred embodiment, the gradient of light transmission can vary over depth within a range of 0.5 mm.
[0028] The dental bulk block according to one embodiment of the present invention is characterized by L by color difference analysis with respect to depth. * , a * and b *The color deviation (ΔE) value can change even within a range of 1.5 mm relative to the depth.
[0029] The dental bulk block according to one preferred embodiment may have a crystallinity of 40 to 80%.
[0030] According to a specific embodiment, the dental bulk block contains 50 to 90 vol.% of lithium disilicate crystalline phase and 10 to 40 vol.% of eucryptite crystalline phase based on the volume of the entire crystalline phase. In another example, the dental bulk block may further contain up to 5 vol.% of lithium phosphate crystalline phase.
[0031] Furthermore, the dental bulk block according to one embodiment of the present invention may have a gradient of bending strength with respect to depth.
[0032] In a preferred embodiment, the flexural strength gradient may be in the range of 210 MPa to 510 MPa.
[0033] A dental bulk block according to one embodiment of the present invention can be made of a continuous glass matrix.
[0034] In a preferred embodiment, the glass matrix contains 69.0 to 78.0 wt% of SiO2, 12.0 to 14.0 wt% of Li2O, 5.5 to 10 wt% of Al2O3, 0.21 to 0.6 wt% of ZnO, 2.0 to 3.5 wt% of K2O, 0.3 to 1.0 wt% of Na2O, 0.1 to 0.5 wt% of SrO, 0.3 to 1.0 wt% of CaO, 0.1 to 2.0 wt% of La2O3, and 2.0 to 6.0 wt% of P2O5, and the molar ratio of Al2O3 / (K2O+ZnO) can satisfy 1.2 to 2.2.
[0035] In another embodiment of the present invention, a method for producing a block of a predetermined shape includes the steps of melting a glass composition containing 69.0 to 78.0 wt% SiO2, 12.0 to 14.0 wt% Li2O, 5.5 to 10 wt% Al2O3, 0.21 to 0.6 wt% ZnO, 2.0 to 3.5 wt% K2O, 0.3 to 1.0 wt% Na2O, 0.1 to 0.5 wt% SrO, 0.3 to 1.0 wt% CaO, 0.1 to 2.0 wt% La2O3, and 2.0 to 6.0 wt% P2O5, wherein the molar ratio of Al2O3 / (K2O+ZnO) satisfies 1.2 to 2.2, forming the glass composition in a mold, cooling the glass composition, and annealing the glass composition at a predetermined rate at 480°C to 250°C for 20 minutes to 2 hours;
[0036] and heat treating the block in a temperature range of 740 to 850°C while applying a temperature gradient in the depth direction of the block.
[0037] In a preferred embodiment of a method for manufacturing a dental bulk block, the heat treatment step can be performed by applying a temperature range of 800 to 850°C to the upper layer of the block and a temperature range of 740 to 760°C to the lower layer of the block.
[0038] In a preferred embodiment, the heat treatment step may be performed in a gradient heat treatment furnace at an operating temperature of 800 to 1000° C. for 1 to 40 minutes.
[0039] Furthermore, one embodiment of the present invention provides a method for manufacturing a dental restoration, comprising the steps of processing the dental bulk block using a processing machine to manufacture a predetermined dental restoration, and polishing or glazing the block.
[0040] In a method for manufacturing a dental restoration according to a preferred embodiment, glazing can be performed at 730 to 820°C for 30 seconds to 10 minutes.
[0041] In another embodiment of the method for manufacturing a dental restoration, glazing can be used to adjust the translucency of the processed dental restoration through heat treatment at a temperature of at least 825° C. Preferably, glazing is performed at a temperature of at least 825° C. for 1 to 20 minutes. [Effects of the Invention]
[0042] The dental bulk block according to the present invention can be easily used to manufacture artificial tooth restorative materials with multi-gradation transparency or physical properties similar to those of natural teeth, so that they can be repeatedly produced without the need for additional processes such as cutting processes using CAD / CAM. This not only shortens the time and process required to manufacture artificial tooth prostheses, but also provides the effect of increased structural stability in terms of force distribution due to the gradient function of mechanical physical properties. Such dental bulk blocks have the advantage that they can be manufactured through a simple method of gradient heat treatment using a single glass composition with a specific composition. [Brief explanation of the drawings]
[0043] [Figure 1] 1 is a graph showing the results of X-ray diffraction analysis of the bulk block of the present invention. [Figure 2] 1 is a scanning electron microscope (SEM) photograph showing the microstructure and crystalline phase size according to depth of a bulk block of the present invention. [Figure 3] 1 is a graph showing the visible light transmittance measurement of a 1.5 mm thick slice test piece of the bulk block of the present invention. [Figure 4] 1 is a comparative graph of cutting resistance for a bulk block of the present invention. [Figure 5] 1 is a schematic diagram showing a method for producing a dental bulk block of the present invention as an example. [Figure 6] 1 is a graph showing the grain size of the main crystalline phase according to the depth of a bulk block obtained according to an embodiment of the present invention. [Figure 7]1 is a graph showing a change in biaxial flexure strength according to depth of a bulk block obtained according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0044] The above and additional aspects of the present invention will become more apparent from the following detailed description of preferred embodiments thereof, which are provided with reference to the accompanying drawings, in which:
[0045] The dental bulk block of the present invention is a glass ceramic block containing a crystalline phase within an amorphous glass matrix, wherein the main crystalline phase is lithium disilicate and the additional crystalline phase includes eucryptite, and is a functionally gradient material having a gradient in the size of the main crystalline phase with respect to depth, with no interface present at the point where the gradient value of the main crystalline phase size changes.
[0046] In the above and following descriptions, the term "main crystalline phase" is defined as a crystalline phase that occupies at least 50% by weight of the total crystalline phase, and the term "additional crystalline phase" can be defined as the remaining crystalline phase in the total crystalline phase that is not the main crystalline phase.
[0047] The content of the crystalline phase can be calculated by X-ray diffraction analysis. For example, the ratio F of the crystalline phase a in a test piece consisting of two polymorphic phases a and b can be calculated as follows: a is quantitatively expressed by the following formula 1.
[0048]
number
[0049] This value can be determined by measuring the intensity ratio of the two crystalline phases and obtaining an integer K, which is the absolute intensity ratio I of the two pure polymorphic forms. oa / I ob and is determined by measuring a standard substance.
[0050] In the above and following descriptions, the term "main crystalline phase" can be defined as being set based on the content calculated by this method.
[0051] Furthermore, "having a gradient of the main crystalline phase size with respect to the depth" means that when the main crystalline phase size is graphed against the depth of the bulk block, there is a gradient of change in the main crystalline phase size, i.e., the main crystalline phase size is expressed in a gradational form with respect to the depth of the bulk block.
[0052] In addition, the "point where the gradient value of the main crystalline phase size changes" refers to a point where the gradient value of the change in the main crystalline phase size substantially changes when the main crystalline phase size is graphed against the depth of the bulk block. Here, the term "substantially changes" may refer to a change in a single numerical value, but may also include a substantial change in the distribution of values.
[0053] Furthermore, the phrase "there is no interface at the location where the gradient value of the main crystalline phase size changes" can be interpreted as meaning that there is no significant boundary surface indicating interlayer separation at the depth of the bulk block where the gradient value of the main crystalline phase size changes. In other words, it means that the bulk block has a gradient of the main crystalline phase size in a continuous form without an interface with depth.
[0054] On the other hand, a "functionally gradient material (FGM)" usually refers to a material in which the properties of the constituent materials change continuously from one surface to another. In the present invention, there is essentially no interface, but the properties of the constituent materials change continuously, so the term "functionally gradient material" is used.
[0055] In the above and following descriptions, it goes without saying that the bulk block is not limited in shape and can include various types of bulk bodies, such as a block type, an ingot type, a cylinder type, etc.
[0056] The bulk block according to the present invention has a predominant crystalline phase of lithium disilicate, eucryptite as an additional crystalline phase, and may contain lithium phosphate as another additional crystalline phase.
[0057] The XRD analysis result graph for the bulk block according to a preferred embodiment is shown in FIG.
[0058] 1, the dental bulk block according to one embodiment of the present invention has a primary crystalline phase of lithium disilicate, and additional crystalline phases, such as major peaks at 2θ = 19.8 and 25.7 degrees, are interpreted as eucryptite (beta-eucryptite, JCPDS#12-0709).
[0059] In the dental bulk block according to one embodiment of the present invention disclosed herein, in addition to eucryptite, an additional crystalline phase exhibits major peaks at 2θ=22.18, 22.9 (degrees), which can be defined as lithium phosphate (JCPDS#15-0760, major peaks at 2θ=22.3, 23.1).
[0060] In the above and following descriptions, XRD analysis will be understood to refer to the results of analysis using an X-ray diffraction analyzer (D / MAX-2500, manufactured by Rigaku Corporation, Japan; CuKα (40 kV, 60 mA), scanning rate: 6° / min, 2θ: 10 to 60 (degrees), manufactured by Rigaku Corporation, Japan).
[0061] Eucryptite is a lithium aluminum silicate (LAS) crystalline phase with the chemical formula LiAlSiO4. Compared to other LAS-based materials such as spodumene (LiAlSiO6), orthoclase (LiAlSiO3O8), or petalite (LiAlSiO4O8), eucryptite exhibits lower cutting resistance to machining tools due to residual thermal stress. The presence of this crystalline phase can result in lower tool wear rates than when lithium disilicate is present alone. This lower tool resistance not only improves cutting efficiency and minimizes wear on milling tools, but also minimizes chipping during machining.
[0062] The crystalline phase constituting the bulk block of the present invention can be formed into microcrystals, which exhibit various sizes and size distributions depending on the temperature, and have the characteristic of being able to realize various mechanical properties and optical transparency.
[0063] Furthermore, by having a gradient in the size of the main crystalline phase with respect to depth, the bulk block can achieve a gradient in translucency and mechanical properties with respect to depth. Moreover, since there is no interface at the point where the gradient value of the size of the main crystalline phase changes, processing by interlayer bonding is unnecessary and the problem of layer separation during cutting can be solved. Furthermore, this type of functional gradation can provide an artificial tooth prosthesis with increased structural stability in terms of force distribution.
[0064] In such a bulk block of the present invention, the gradient of the main crystal phase size can be realized within the range of an average grain size of 0.02 μm to 1.5 μm.
[0065] As an example, Figure 2 shows a scanning electron microscope (SEM) photograph of a dental bulk block of the present invention, with the left side of Figure 2 showing an SEM photograph of the lower part of the block (20 mm deep), the center of Figure 2 showing an SEM photograph of the middle part of the block (10 mm deep), and the right side of Figure 2 showing an SEM photograph of the upper part of the block (0.5 mm deep).
[0066] The average size of the crystalline phase particles can be derived from the SEM photograph obtained in this way. Specifically, the average size can be calculated by drawing a diagonal line or a random straight line on the SEM photograph, dividing the number of crystalline phases that the line passes through by the length of the line, and taking the magnification into consideration, using the linear intercept method.
[0067] In the above and following descriptions, it will be understood that the size of the crystalline phase is calculated by such a method.
[0068] The bulk block of the present invention is a functionally gradient material, and since such a functionally gradient material is applied to cutting processes, such as CAD / CAM processing, under the same processing conditions, taking into consideration machinability and the ability to exhibit permeability sufficient for clinical use as an artificial tooth restoration material, it is preferable that the gradient in the size of the main crystalline phase be realized within the range of an average particle size of 0.02 μm to 1.5 μm.
[0069] The dental bulk block of the present invention has a gradient in the size of the main crystalline phase as described above, and therefore has a gradient in light transmittance with respect to depth.
[0070] In particular, when the range of average particle diameter is taken into consideration in the gradient of the above-mentioned crystalline size, the gradient of light transmittance can be in the range of 22 to 35% based on a wavelength of 550 nm.
[0071] In the above and following descriptions, the light transmittance was measured using a UV-visible spectrometer (UV-2401PC, Shimadzu Corporation, Japan).
[0072] As described above, the dental bulk block of the present invention does not have an interface at the point where the gradient value of the main crystalline phase size changes, so from this perspective, it can be confirmed that the gradient of light transmittance changes within a range of 0.5 mm relative to the depth, and actually changes within a range of 1.5 mm relative to the depth.
[0073] To measure the optical transmittance at each gradient position in the dental bulk block according to the present invention, a section of approximately 1.5 mm was cut in the depth direction where the transparency decreased, and the surface of the specimen was wiped clean with ethanol. The specimen was then measured using a UV-visible spectrometer (UV-2401PC, Shimadzu Corporation, Japan). The measurement wavelength range was 300-800 nm, and the slit width was 2.0 nm. The difference in transmittance for the 1.5 mm-thick slice specimens can be seen from the results in Figure 3.
[0074] In FIG. 3, each test piece corresponds to a test piece by depth in Table 1 below.
[0075] [Table 1]
[0076] These results indicate that the light transmittance value changes even within a 1.5 mm depth range, i.e., gradient transmittance is observed even at this thickness. This result clearly demonstrates that the dental bulk block of the present invention is a functionally gradient material. Furthermore, when fabricating a prosthesis such as a crown, the area corresponding to the bridgehead is processed to the thickest thickness, so it is expected that aesthetically pleasing light transmittance will be exhibited even at this thickness range.
[0077] From another point of view, the dental bulk block of the present invention has a gradient in shade, so that the L by color difference analysis with respect to depth can be obtained. * , a * and b *As described above, in the dental bulk block of the present invention, there is no interface at the point where the gradient value of the main crystalline phase size changes, and from this perspective, it can be confirmed that the color deviation (ΔE) value changes even within a depth range of 1.5 mm.
[0078] Color standardization was needed for accurate measurement, transmission, and reproduction of colors. For this reason, color systems were devised. Many color systems have been proposed, and the most widely used to date is the CIE L system, established by the International Commission on Illumination (CIE) in 1976. * a * b * CIELAB color space, where L * indicates lightness, and a * and b * indicates chromaticity coordinates. In the coordinates, L * Increasing values indicate brighter colors, decreasing values indicate darker colors, and +a * is red, -a * is green, +b * is yellow, -b * means blue, respectively.
[0079] To measure the color at each gradient position in the dental bulk block according to the present invention, the specimen was cut at a depth of approximately 1.5 mm in the direction of decreasing transparency, and the surface of the specimen was wiped clean with ethanol and analyzed using a UV-visible spectrometer (UV-2401PC, Shimadzu Corporation, Japan). The measurement wavelength range was 380-780 nm, and the slit width was 2.0 nm. After setting a baseline using a reference sample, the reflectance of the specimen was measured to obtain the L. * a * b * The measured L * a * b *To reduce errors, measurements were taken three times and the average value was used. These three values were used to calculate ΔE, which indicates the color difference. A ΔE value of 0 between two test pieces means there is no color difference, while values between 0 and 2 mean there is a very slight color difference. Values between 2 and 4 mean the color difference is noticeable, and values between 4 and 6 mean the color difference is appreciable. Values between 6 and 12 mean the color difference is very large, and values above 12 mean the color difference is very much.
[0080] For a dental bulk block shown in Figures 1 and 2, which is a glass-ceramic block containing a crystalline phase within an amorphous glass matrix, the crystalline phase includes a primary crystalline phase of lithium disilicate and an additional crystalline phase of eucryptite, and which is a functionally gradient material with a gradient in the size of the primary crystalline phase with respect to depth and no interface where the gradient in the size of the primary crystalline phase changes, the results in Table 2 below confirm that a 0.31 mm-thick sliced specimen exhibits a color deviation (ΔE) of 1.4 to 1.6 with respect to depth. This result is considered to mean that the color deviation (ΔE) value changes even within a 1.5 mm depth range, i.e., that a gradient shade of different colors appears even within this thickness. From another perspective, this result clearly demonstrates that the dental bulk block of the present invention is a functionally gradient material.
[0081] [Table 2]
[0082] The dental bulk block of the present invention also has a depth-dependent flexural strength gradient. In particular, considering the range of average grain size in the crystalline size gradient described above, the flexural strength gradient can be in the range of 210 MPa to 510 MPa.
[0083] Meanwhile, in consideration of the ability to realize the functional gradient of the various physical properties described above and processability, the dental bulk block of the present invention may preferably have a crystallinity of 40 to 80%.
[0084] In the above and following descriptions, "crystallinity" can be defined as the ratio of the crystalline phase to the amorphous glass matrix, which can be determined by various methods. In one embodiment of the present invention, this is a value automatically calculated using an X-ray diffraction analyzer.
[0085] Such a dental bulk block of the present invention is a glass ceramic in which a crystalline phase is precipitated within a continuous amorphous glass matrix, and the main crystalline phase is lithium disilicate, and the additional crystalline phase contains a crystalline phase containing eucryptite, and a functionally gradient material can be obtained that has a gradient in the size of the main crystalline phase with respect to depth, and no interface exists where the gradient value of the main crystalline phase size changes.
[0086] In particular, the crystalline phase preferably contains 50 to 90 vol.% of lithium disilicate crystalline phase and 10 to 40 vol.% of eucryptite crystalline phase as an additional crystalline phase, based on the volume of the entire crystalline phase. When lithium phosphate is contained as an additional crystalline phase, its content preferably does not exceed a maximum of 5 vol.%.
[0087] As mentioned above, the eucryptite crystalline phase can improve the machinability of glass ceramics having lithium disilicate as the main crystalline phase, but if its content is excessive, it may reduce strength. Therefore, taking into consideration machinability and strength, the content of eucryptite in the crystalline phase is preferably 10 to 40 vol.% based on the volume of the entire crystalline phase.
[0088] In the above and following descriptions, the term "continuous glass matrix" can be defined as a glass matrix in which there are no interlayer interfaces and the composition of the glass matrix is the same throughout the entire block.
[0089] Specifically, a preferred glass matrix contains 69.0 to 78.0 wt% of SiO2, 12.0 to 14.0 wt% of Li2O, 5.5 to 10 wt% of Al2O3, 0.21 to 0.6 wt% of ZnO, 2.0 to 3.5 wt% of K2O, 0.3 to 1.0 wt% of Na2O, 0.1 to 0.5 wt% of SrO, 0.3 to 1.0 wt% of CaO, 0.1 to 2.0 wt% of La2O3, and 2.0 to 6.0 wt% of P2O5, and the molar ratio of Al2O3 / (K2O+ZnO) can satisfy 1.2 to 2.2.
[0090] Glass compositions undergo heat treatment for crystallization, which generates crystal nuclei and crystal growth, resulting in the precipitation of a crystalline phase within an amorphous glass matrix. The temperature at which crystal nuclei and growth occur for the glass matrix described above is between 500°C and 850°C. Crystal nuclei begin to form at a minimum of 500°C, and crystal growth occurs as the temperature rises. This crystal growth reaches a maximum of 850°C, resulting in the lowest optical transparency for use as an artificial tooth. Since optical transparency gradually decreases from the crystal growth temperature to a maximum of 850°C, focusing on this crystal growth and realizing it in a single bulk block can mimic the multi-gradation of natural teeth.
[0091] Natural teeth, not just one tooth, but all teeth have different translucencies, and if we can embody this change in translucency due to heat treatment temperature in a single bulk block, we can fully realize the multi-gradation of natural teeth.
[0092] From this viewpoint, the present invention provides a method for producing a block of a predetermined shape, comprising the steps of melting a glass composition containing 69.0 to 78.0 wt% SiO2, 12.0 to 14.0 wt% Li2O, 5.5 to 10 wt% Al2O3, 0.21 to 0.6 wt% ZnO, 2.0 to 3.5 wt% K2O, 0.3 to 1.0 wt% Na2O, 0.1 to 0.5 wt% SrO, 0.3 to 1.0 wt% CaO, 0.1 to 2.0 wt% La2O3, and 2.0 to 6.0 wt% P2O5, wherein the molar ratio of Al2O3 / (K2O+ZnO) satisfies 1.2 to 2.2, forming the glass composition in a mold, cooling the glass, and annealing the glass composition at a predetermined rate at 480°C to 250°C for 20 minutes to 2 hours;
[0093] and heat treating the block in a temperature range of 740 to 850°C while applying a temperature gradient in the depth direction of the block.
[0094] As described above, the glass composition can exhibit different optical translucency characteristics depending on the range of heat treatment temperatures. Therefore, when the heat treatment is applied uniformly to the entire block, the glass composition exhibits a constant optical translucency. However, when the heat treatment is applied to the block with a temperature gradient, the glass composition can exhibit multigradation of physical properties or optical translucency in one block.
[0095] Bulk-type blocks are used as workpieces for machining, such as CAD / CAM processing. In the manufacturing method of the present invention, when heat-treating the block, a temperature gradient is applied in the depth direction, thereby producing a bulk block with multi-gradation in translucency and strength.
[0096] Conventional crystallized glass generally has large crystal sizes, making it difficult to adjust translucency, and is also strong, making it difficult to process. In contrast, the glass composition used in the present invention can form microcrystals, which show various sizes and size distributions depending on the temperature, resulting in diverse physical properties and translucency. Taking this into account, a block is made from a single glass composition, and then heat-treated under a temperature gradient, allowing for the realization of multi-gradations in mechanical properties and translucency in a single bulk block.
[0097] Here, the "step of heat-treating the block by applying a temperature gradient in the depth direction" means not only applying a temperature gradient that gradually increases from the bottom to the top in the depth direction of the block, but also a temperature gradient in the form of applying a temperature difference in parts. It goes without saying that the selection of such a temperature gradient method can be varied depending on the characteristics of the natural teeth of the patient requiring the artificial tooth prosthesis, or can be varied depending on the unique characteristics of the tooth portion requiring the prosthesis.
[0098] However, in consideration of normal natural teeth, it is preferable to perform the heat treatment by applying a temperature gradient in a manner that the temperature gradually increases from the bottom to the top of the block depth.
[0099] As a preferred example, the heat treatment step is performed by applying a temperature range of 800 to 850°C to the upper layer of the block and a temperature range of 740 to 760°C to the lower layer of the block. Due to this temperature gradient, the heat treatment step is preferably performed in a gradient heat treatment furnace at an operating temperature of 800 to 1000°C for 1 to 40 minutes.
[0100] When the above-described glass composition and the heat treatment method of the present invention are used, it is possible to mimic the characteristic of natural tooth structure, which has low translucency at the cervical side and increases translucency toward the incisal side, which is economically advantageous since separate characterization is not required during prosthesis fabrication as in conventional methods.
[0101] In addition, the physical properties of natural teeth are such that the enamel, which is the surface layer, has high bending strength, while the dentin inside it has low strength, and therefore plays a role in absorbing and dispersing external forces. However, in the present invention, it is possible to create a functionally gradient material in which the mechanical properties, especially bending strength, have a gradient due to differences in the microstructure depending on the depth of heat treatment, and therefore it is possible to reproduce the physical properties of natural teeth very closely.
[0102] Manufacturing dental restorations using the dental bulk block obtained by the present invention can be expected to result in significant improvements in processability.As a specific example, in one embodiment of the present invention, a method for manufacturing a dental restoration is provided, which includes the steps of processing the above-mentioned dental bulk block using a processing machine to manufacture a predetermined dental restoration, and polishing or glazing the block.
[0103] In the above and following descriptions, dental restorations include all crowns, inlays, onlays, veneers, abutments, and the like.
[0104] Glazing can be performed at 730-820°C for 30 seconds to 10 minutes, which is a typical finishing heat treatment step that causes little change in translucency. Glazing is usually performed within a range that does not change the inherent translucency of the bulk block, and the glazing heat treatment can increase strength by 50% or more by relaxing surface microcracks (surface healing).
[0105] However, in one specific embodiment, in the method for manufacturing a dental restoration using the bulk block according to the present invention, glazing can be used to adjust the translucency of the processed dental restoration through a heat treatment at least at 825° C. In other words, after the bulk block is processed to manufacture a dental restoration, glazing can be utilized in an application in which the translucency can be reduced to adjust the brightness in the final finishing step.
[0106] When a bulk block is machined by a fabricator or user to manufacture a dental restoration, it may unintentionally change to a high translucency. In such cases, with a conventional lithium disilicate bulk block, the processed bulk block must be discarded, and then reprocessed through a predetermined heat treatment to obtain a bulk block with the desired translucency, which must then be processed into a dental restoration. However, the bulk block of the present invention is a unique bulk block with a fine crystalline phase that exhibits a property that allows its translucency to be adjusted depending on the heat treatment temperature. Therefore, reprocessing is not required, and the translucency can be easily adjusted by glazing the block under predetermined conditions as a final finishing step for the processed dental restoration. This also allows for a simple method of concealing tooth discoloration that may occur during processing into a dental restoration through glazing.
[0107] Glazing for such applications is preferably carried out at a temperature of at least 825°C for a period of 1 to 20 minutes.
[0108] Characteristically, the dental bulk block obtained by the present invention can significantly reduce the resistance generated in the tool during processing using a processing machine. As a specific example, a dental bulk block (present invention) is a glass ceramic block containing a crystalline phase in an amorphous glass matrix as shown in Figures 1 and 2, where the crystalline phase is a functionally gradient material in which the crystalline phase has a gradient in size of the main crystalline phase with respect to depth and no interface exists where the gradient value of the main crystalline phase size changes. The dental bulk block (present invention) was cut to a size of 12 x 14 x 18 mm and rotated at 250 RPM using a low-speed saw (ISOMET low-speed saw, Buehler, Germany) and a diamond electroplated wheel (2514485H17, Norton, USA), and the cutting time was measured. Using the same method, the cutting times were measured for the most common lithium disilicate block (conventional lithium disilicate, manufactured by HASS Corp.), the zirconia-reinforced lithium disilicate bulk block (Celtra Duo, manufactured by DentsplySiron), and the lithium aluminosilicate-reinforced lithium disilicate bulk block (LAS-reinforced lithium disilicate) (Nice, manufactured by Straumann).
[0109] The cutting resistance (%) was calculated from each of the obtained cutting time values. Specifically, the cutting time obtained for a general lithium disilicate block was set as 100%, and the cutting time was converted into a relative percentage, which was then used to calculate each cutting resistance value.
[0110] The results are shown in Figure 4.
[0111] 4, it was confirmed that the cutting resistance of the general lithium disilicate block was the highest, followed by LAS (lithium aluminosilicate) glass-ceramics and zirconia-reinforced glass-ceramics, and that the cutting resistance of the block according to the present invention was significantly lower. From these results, it can be predicted that the glass-ceramic block according to the present invention is the most machinable, and this is due to the inclusion of eucryptite as an additional crystalline phase.
[0112] In one specific embodiment of the present invention, a glass composition containing 69.0 to 78.0 wt% SiO2, 12.0 to 14.0 wt% Li2O, 5.5 to 10 wt% Al2O3, 0.21 to 0.6 wt% ZnO, 2.0 to 3.5 wt% K2O, 0.3 to 1.0 wt% Na2O, 0.1 to 0.5 wt% SrO, 0.3 to 1.0 wt% CaO, 0.1 to 2.0 wt% La2O3, and 2.0 to 6.0 wt% P2O5, and having a molar ratio of Al2O3 / (K2O+ZnO) of 1.2 to 2.2, is first weighed and mixed.
[0113] When added to silicate glass, Al2O3 occupies tetrahedral sites and acts as a glass former, increasing viscosity and reducing ion mobility. In contrast, K2O, ZnO, CaO, and La2O decrease viscosity and increase ion mobility. As ion mobility increases, it is expected that eucryptite will grow preferentially. Furthermore, increasing the amount of modifiers such as ZnO increases ion mobility. When excessive SiO2 is added, minor crystalline phases such as eucryptite precipitate within the glass matrix along with the main crystalline phase, lithium disilicate. From this perspective, a molar ratio of Al2O3 / (K2O + ZnO) of 1.2 to 2.2 is preferred for providing the bulk block of the present invention containing eucryptite as an additional crystalline phase.
[0114] Li2CO3 can be added to the glass composition instead of Li2O, and carbon dioxide (CO2), the carbon (C) component of Li2CO3, is released as a gas during the glass melting process. Also, K2CO3 and Na2CO3 can be added to the alkali oxides instead of K2O and Na2CO3, respectively, and carbon dioxide (CO2), the carbon (C) component of K2CO3 and Na2CO3, is released as a gas during the glass melting process.
[0115] The mixing is performed using a dry mixing process, which may be a ball milling process. Specifically, the starting materials are loaded into a ball milling machine, which rotates at a constant speed to mechanically pulverize and uniformly mix the starting materials. The balls used in the ball milling machine may be made of a ceramic material such as zirconia or alumina, and may all be the same size or have at least two sizes. The ball size, milling time, and rotation speed of the ball milling machine are adjusted based on the target particle size. For example, the ball size may be set to a range of approximately 1 mm to 30 mm, and the rotation speed of the ball milling machine may be set to a range of approximately 50 to 500 rpm. The ball milling is preferably performed for 1 to 48 hours based on the target particle size. The starting materials are pulverized into fine particles with a uniform particle size and uniform mixing.
[0116] The mixed starting materials are placed in a melting furnace, and the furnace is heated to melt the starting materials. Here, "melting" refers to the starting materials changing from a solid state to a viscous liquid state. The melting furnace is preferably made of a material that has a high melting point, high strength, and a low contact angle to prevent the molten material from sticking together. For this reason, the melting furnace is preferably made of a material such as platinum (Pt), diamond-like carbon (DLC), or chamotte, or its surface is coated with a material such as platinum (Pt) or diamond-like carbon (DLC).
[0117] Melting is preferably carried out at 1,400 to 2,000°C under normal pressure for 1 to 12 hours. If the melting temperature is below 1,400°C, the starting materials may not be melted, while if the melting temperature is above 2,000°C, excessive energy consumption is required, which is uneconomical. Therefore, melting within the above-mentioned temperature range is preferred. Furthermore, if the melting time is too short, the starting materials may not be melted sufficiently, while if the melting time is too long, excessive energy consumption is required, which is uneconomical. The temperature rise rate of the melting furnace is preferably about 5 to 50°C / min. However, if the temperature rise rate of the melting furnace is too slow, it takes too long and productivity is reduced. If the temperature rise rate of the melting furnace is too fast, the sudden temperature rise may result in excessive volatilization of the starting materials, which may result in poor physical properties of the crystallized glass. Therefore, it is preferable to raise the temperature of the melting furnace at a rate within the above-mentioned range. Melting is preferably carried out in an oxidizing atmosphere such as oxygen (O2) or air.
[0118] The molten material is poured into a predetermined mold to obtain dental glass-ceramics of the desired shape and size. The mold is preferably made of a material that has a high melting point, high strength, and a low contact angle to prevent the glass melt from sticking to it. For this purpose, the mold is preferably made of a material such as graphite or carbon, and is preferably preheated to 200 to 300°C to prevent thermal shock before pouring the molten material into the mold.
[0119] As the molten material placed in the mold is shaped and cooled, it is preferable to carry out an annealing step at a predetermined rate for 20 minutes to 2 hours at 480°C to 250°C after the cooling process. This annealing step reduces stress variations within the molded product, preferably eliminating stress, and has a favorable effect on controlling the size of the crystalline phase and improving the uniformity of the crystal distribution in the subsequent crystallization step, ultimately resulting in the production of the desired functionally gradient material.
[0120] Here, the predetermined rate is preferably 2.3 to 14°C / min, as this allows for sufficient slow cooling.
[0121] The molded product thus subjected to the slow cooling process is transferred to a crystallization heat treatment furnace, where nucleation and crystal growth occur to produce the desired crystallized glass.
[0122] FIG. 5 shows a schematic diagram of a method for performing crystallization heat treatment by applying a temperature gradient according to the present invention. When performing crystallization heat treatment on a block-type or ingot-type bulk block, a temperature gradient is applied along the depth direction so that high-temperature heat treatment is performed at the upper end and low-temperature heat treatment is performed at the lower end.
[0123] In the above and following descriptions, the step of applying a temperature gradient to heat treatment is not limited to a specific device or method, but may be performed in, for example, a gradient heat treatment furnace. Considering the heat treatment temperature, it is preferable that the operating temperature be 900 to 1,100°C.
[0124] This temperature gradient heat treatment results in a gradient in light transmittance from the high temperature region to the low temperature region, and a gradient in flexural strength from the low temperature region. This is because the crystal size within the glass-ceramic can be adjusted depending on the temperature. The crystalline phase produced after the temperature gradient heat treatment contains lithium disilicate as the main crystalline phase and eucryptite as an additional crystalline phase, and can be produced with a size gradient of the main crystalline phase with an average grain size of 0.02 μm to 1.5 μm.
[0125] Meanwhile, the crystalline grain size versus depth of the bulk block obtained according to the present invention was analyzed and the results are shown in FIG.
[0126] The change in bending strength with respect to the depth of the bulk block obtained according to the present invention was measured and is shown in FIG.
[0127] While the present invention has been described with reference to one embodiment shown in the drawings, this embodiment is by way of example only, and those skilled in the art will recognize that various modifications and equivalent alternative implementations are possible from this embodiment. [Industrial Applicability]
[0128] The present invention relates to a dental bulk block useful for producing artificial teeth that resemble the structural characteristics of natural teeth, and in particular to a dental bulk block with improved machinability, and a method for producing the same. The dental bulk block of the present invention can be easily used to manufacture artificial tooth restorative materials with multi-gradation transparency or physical properties similar to those of natural teeth, so that they can be repeatedly produced without the need for additional processes such as cutting processes using CAD / CAM. This not only shortens the time and process required to manufacture artificial tooth prostheses, but also provides the effect of increased structural stability in terms of force distribution due to the gradient function of mechanical physical properties.Such dental bulk blocks have the advantage that they can be manufactured through a simple method of gradient heat treatment using a single glass composition with a specific composition.
Claims
1. 1. A glass-ceramic block comprising a crystalline phase within an amorphous glass matrix, comprising: The crystalline phase comprises a predominant crystalline phase of lithium disilicate and an additional crystalline phase of eucryptite; A functionally gradient material having a gradient of the main crystal phase size with respect to depth, and no interface is present at the location where the gradient value of the main crystal phase size changes, The glass matrix of the glass ceramic block contains 69.0-78.0 wt% SiO2, 12.0-14.0 wt% Li2O, 5.5-10 wt% Al2O3, 0.21-0.6 wt% ZnO, 2.0-3.5 wt% K2O, 0.3-1.0 wt% Na2O, 0.1-0.5 wt% SrO, 0.3-1.0 wt% CaO, 0.1-2.0 wt% La2O3, and 2.0-6.0 wt% P2O5, and the molar ratio of Al2O3 / (K2O+ZnO) satisfies 1.2-2.
2. A dental bulk block comprising:
2. The gradient of the main crystal phase size is realized within the range of average grain size of 0.02 μm to 1.5 μm.
2. The dental bulk block of claim 1.
3. Has a gradient of light transmittance with respect to depth 2. The dental bulk block of claim 1.
4. The gradient of the light transmittance is in the range of 22-35% based on a wavelength of 550 nm.
4. The dental bulk block according to claim 3.
5. The gradient of light transmittance changes within a range of 0.5 mm relative to the depth.
4. The dental bulk block according to claim 3.
6. L by color difference analysis for depth * , a * and b * The color deviation (ΔE) value changes even within a range of 1.5 mm relative to the depth.
2. The dental bulk block of claim 1.
7. The crystallinity is 40-80%.
2. The dental bulk block of claim 1.
8. The crystalline phase contains 50 to 90 vol. % of lithium disilicate crystalline phase and 10 to 40 vol. % of eucryptite crystalline phase based on the volume of the entire crystalline phase. A dental bulk block according to claim 1 or 7.
9. Has a gradient of bending strength with respect to depth 2. The dental bulk block of claim 1.
10. The gradient of bending strength is in the range of 210 MPa to 510 MPa.
10. The dental bulk block of claim 9.
11. Dental bulk blocks are made of a continuous glass matrix.
2. The dental bulk block of claim 1.
12. SiO 2 69.0-78.0% by weight, Li 2 O12.0-14.0% by weight, Al 2 O 3 5.5-10% by weight, ZnO 0.21-0.6% by weight, K 2 O2.0-3.5% by weight, Na 2 O0.3-1.0% by weight, SrO0.1-0.5% by weight, CaO0.3-1.0% by weight, La 2 O 3 0.1 to 2.0% by weight and P 2 O 5 2.0 to 6.0 wt. % Al 2 O 3 / (K 2 The method includes the steps of melting a glass composition having a molar ratio of 1.2 to 2.2 (ZnO+ZnO), forming the glass composition in a mold, cooling the glass composition, and annealing the glass composition at a predetermined rate for 20 minutes to 2 hours at 480° C. to 250° C., thereby producing a block of a predetermined shape; and heat treating the block at a temperature in the range of 740 to 850° C. while applying a temperature gradient in the depth direction of the block. A method for manufacturing a dental bulk block, comprising the steps of:
13. The heat treatment step is performed such that the upper layer of the block is subjected to a temperature range of 800 to 850° C. and the lower layer of the block is subjected to a temperature range of 740 to 760° C. A method for producing the dental bulk block according to claim 12.
14. The heat treatment step is carried out in a gradient heat treatment furnace at an operating temperature of 800 to 1,000° C. for 1 to 40 minutes. A method for producing a dental bulk block according to claim 12 or 13.
15. A step of manufacturing a predetermined dental restoration by machining the dental bulk block for cutting according to claim 1 using a machining machine; and polishing or glazing the dental restoration. A method for producing a dental restoration comprising the steps of:
16. Glazing is carried out at 730-820°C for 30 seconds to 10 minutes. A method for producing a dental restoration according to claim 15.
17. Glazing is an application for adjusting the translucency of a fabricated dental restoration via a heat treatment of at least 825°C. A method for producing a dental restoration according to claim 15.
18. Glazing is carried out at a temperature of at least 825°C for 1 to 20 minutes. A method for producing a dental restoration according to claim 17.
Citation Information
Patent Citations
Method for forming dental restorative material and related device
JP2001288027A
Method for molding dental restoration material and related apparatus
JP2006089502A
Method of reducing time for machining dental ceramic blank
JP2011062526A
X-ray opaque barium-free glass and use of the same
JP2013087054A
Dental crystallized glass block with an upper structure connected thereto and method for producing the same
JP2017531607A
